2020
DOI: 10.1111/1346-8138.15196
|View full text |Cite
|
Sign up to set email alerts
|

Japanese guidance for use of biologics for psoriasis (the 2019 version)

Abstract: As the first biologics for psoriasis in Japan, infliximab and adalimumab, anti‐tumor necrosis factor‐α antibodies, became available in the field of dermatology in 2010, followed by ustekinumab, an anti‐interleukin (IL)‐12/IL‐23p40 antibody, which was launched in Japan in 2011. Since 2015, three IL‐17 inhibitors of secukinumab and ixekizumab, anti‐IL‐17A antibodies, and brodalumab, an anti‐IL‐17 receptor antibody, and two anti‐IL‐23p19 antibodies of guselkumab and risankizumab, have also been launched. It is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(114 citation statements)
references
References 79 publications
3
109
2
Order By: Relevance
“…Despite the limitations, this study received cooperation from as many as 100 sites across Japan and the demographics are not particularly different from an epidemiological study in Japanese PsO patients; 35 the results of this study could be generalized to reflect the safety and effectiveness of secukinumab in real‐word clinical use in Japan. A recent report of a Japanese psoriasis guideline for use of biologics states that it is important for physicians to select appropriate biologic therapy for each psoriatic patient after due consideration of disease factors, treatment factors and patient background factors, and to share such information with patients 18 . This study showed consistent safety profile and effectiveness of secukinumab regardless of the patient characteristics, suggesting that secukinumab can be an appropriate therapy for psoriatic patients after considering various factors of the patients.…”
Section: Discussionmentioning
confidence: 54%
“…Despite the limitations, this study received cooperation from as many as 100 sites across Japan and the demographics are not particularly different from an epidemiological study in Japanese PsO patients; 35 the results of this study could be generalized to reflect the safety and effectiveness of secukinumab in real‐word clinical use in Japan. A recent report of a Japanese psoriasis guideline for use of biologics states that it is important for physicians to select appropriate biologic therapy for each psoriatic patient after due consideration of disease factors, treatment factors and patient background factors, and to share such information with patients 18 . This study showed consistent safety profile and effectiveness of secukinumab regardless of the patient characteristics, suggesting that secukinumab can be an appropriate therapy for psoriatic patients after considering various factors of the patients.…”
Section: Discussionmentioning
confidence: 54%
“…In the USA [ 2 ], the UK [ 30 ] and Japan [ 31 ], currently available biological agents for the treatment of plaque psoriasis include the TNF-α inhibitors infliximab, adalimumab, etanercept (US and UK only) and certolizumab pegol (US and UK only); the IL-12/23 inhibitor ustekinumab; the IL-17 inhibitors secukinumab, ixekizumab and brodalumab; and the IL-23 inhibitors guselkumab, tildrakizumab (US and UK only) and risankizumab [ 2 , 31 ]. European S3 guidelines published prior to the EU approval of risankizumab strongly recommend adalimumab, etanercept, infliximab, ustekinumab and secukinumab for the second-line treatment of plaque psoriasis [ 3 ].…”
Section: Place Of Risankizumab In the Management Of Moderate To Severmentioning
confidence: 99%
“…efficacy and safety) and patient-related factors (e.g. disease severity, comorbidities, personal preferences), as well as drug-related factors such as the route and frequency of administration [ 2 , 30 , 31 ]. All of the newer biological agents approved for plaque psoriasis are administered via subcutaneous injection.…”
Section: Place Of Risankizumab In the Management Of Moderate To Severmentioning
confidence: 99%
“…45 mg every 12 weeks, and 300 mg every month, respectively. 30 It is critical to investigate whether maintenance doses of biologics can be reduced or if the agents could be discontinued.…”
Section: Intermittent Csa Therapymentioning
confidence: 99%
“…Biologics have very good curative effects; however, their high costs and the requirement of subcutaneous injection make it difficult for patients to adhere to medication for a long time. The standard maintenance doses of adalimumab (ADA), etanercept (ETA), infliximab (INF), ustekinumab (UST), and secukinumab have been reported to be 40 mg every fortnightly, 50 mg every week, 5 mg/kg every 8 weeks, 45 mg every 12 weeks, and 300 mg every month, respectively 30 . It is critical to investigate whether maintenance doses of biologics can be reduced or if the agents could be discontinued.…”
Section: Biologicsmentioning
confidence: 99%